Acquisizione d’impresa e fattori culturali: il caso Benelli QJ - Aureli, Selena; DeMartini, Paola (Piccola Impresa / Small Business, 2009)
Following the 'culture-bound' approach, which indicates that national culture impacts the organizational culture and consequently the design of organizational and managerial systems, this research work analyzes the encounter of the Italian and Chinese cultures experienced by Benelli, an Italian firm specialized in motorcycle manufacturing. In particular, it empathizes that international operations of merger and acquisition should consider both strategic and cultural aspects to work successfully and produce the expected results.